Integrated Rice Value Chain Development through Farmer Cooperatives: Coordinating Production, Processing, and Marketing - Ahmad Sabiq Mubarok; Popong Nurhayati; Zenal Asikin (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Increasing market complexity requires stronger coordination across agricultural value chain activities. This study examined the integrated rice value chain developed through farmer cooperatives. The research focused on how production, processing, and marketing activities were coordinated within a cooperative-based rice agribusiness system. A qualitative case study approach was employed at Cooperative Produsen Citra Kinaraya and its farmer-owned enterprise, PT Tasbiha Mulia Tani (PT TMT). Data were collected through in-depth interviews, observations, and documentation involving cooperative managers, PT TMT management, and farmer members. The study applied the value chain mapping approach developed by ACIAR to analyze actors, product flows, information exchange, supporting services, and coordination mechanisms within the value chain. The findings revealed that the rice value chain was organized into three integrated stages: cultivation, processing, and marketing. PT TMT played a central coordinating role by linking farmers with market demand through production planning, processing management, and distribution networks. The study also identified several challenges, including unstable raw material supply, limited expansion of farmer partnerships, and declining partnership attractiveness following government grain pricing policies. Strengthening partnership arrangements and developing risk-sharing mechanisms were identified as important strategies to improve the sustainability of cooperative-based rice value chains.